LRAT overexpression diminishes intracellular levels of biologically active retinoids and reduces retinoid antitumor efficacy in the murine melanoma B16F10 cell line - Amann, Philipp M.; Czaja, Katharina; Bazhin, Alexandr V.; Rühl, Ralph; Eichmüller, Stefan B.; Merk, Hans F.; Baron, Jens Malte (Skin pharmacology and physiology, 2015)
Background/Aim: Vitamin A (alltrans-retinol, ATRol) serves as a precursor for alltrans-retinoic acid (ATRA), a ligand for the retinoic acid receptor (RAR), representing a potent regulator for many physiological processes. While murine melanoma cells are highly sensitive to retinoid treatment, human melanoma cells have developed still unidentified mechanisms that mediate cellular retinoid resistance. One of the key retinoid metabolizing enzymes is lecithin retinol acyltransferase (LRAT), which catalyzes the transformation of ATRol into inactive retinyl esters. LRAT is highly expressed in human melanoma cells. The aim of this study was to identify the mechanisms in retinol metabolism that are responsible for cellular retinoid sensitivity in the murine melanoma cell line B16F10. Methods: mRNA expression analysis, cell viability assessment and determination of intracellular retinoid levels using HPLC analysis of a generated LRAT-overexpressing B16F10 cell line compared to the control B16F10 cell line. Results: We found that the murine retinoid-sensitive B16F10 cell line does not express the enzyme LRAT. LRAT overexpression decreased the antiproliferative effects of retinoid treatment in these melanoma cells. The RAR-regulated enzyme Cyp26a1 showed a significantly lower expression in LRAT-overexpressing B16F10 cells. Cyp26a1 expression was restored after ATRA incubation. HPLC analysis revealed that the level of inactive retinyl ester increased after ATRol treatment, and levels of the substrate ATRol and biologically active ATRA significantly decreased in LRAT-overexpressing murine melanoma. Consistently with this, levels of 4-oxo-retinoic acid, an ATRA metabolite and Cyp26a1 product, were also decreased in LRAT-overexpressing cells. Conclusion: Our results revealed a direct link between LRAT expression and regulation of ATRA levels indicating that the absence of LRAT-catalyzed retinol esterification is important for mediating retinoid sensitivity in murine melanoma cells. Thus, our data suggest that LRAT overexpression represents a novel mechanism by which tumor cells can escape high supplementary ATRA levels that mediate tumor-suppressive RAR signaling.
Gesehen am 28.03.2018